Deconstructing Students’ Language Identities On X: A Nigerian and Malaysian Case Study For Education - Azidah Abu Ziden; Adu Emmanuel Ifedayo (WISE Pendidikan Indonesia, 2024)
This study investigated students’ language deconstruction and identities on X social media technology. The Gen Z’s and Big Data are currently in vogue, which affords this research to enquire using a quantitative methodology. Besides, the online data analytics consisting of the number of likes, repost and comments were gathered from the X social media. Nowadays, the social media acts as an online reservoir for internet data that are readily available for use. Learning analytics are records of students’ activities based on their engagement on social media. However, the respondents in this study were students randomly selected from a two-world perspective on X, consisting of Malaysian and Nigerian students. A detailed data analysis was conducted using the statistical package for social sciences (SPSS) and the results showed a recent decline of students’ engagement in educational discourse using indigenous languages on X. The recent decline was informed by this study’s data, which implies an imminent action is required to ensure the indigenous languages are protected from extinction. This study findings are significant to lecturers, policymakers, researchers and Government in ensuring that more language diversity issues are considered in this 21st century. This research likewise addressed the English language (L2) significance in educational discourse with a recommendation for the inclusion of more indigenous language option on X for diversity and equality purpose.